Azoles resistance of candida species causing vulvo-vaginitis in reproductive age women at a tertiary care setting - Zaman, Ronaq; Ullah, Ihsan; Adeeb, Humera; Arif, Ambreen (Pakistan Journal of Medical Sciences, 2022)
Objectives: To study prevalence and resistance pattern to azoles of candida species causing vulvovaginitis in reproductive age women. Methods: Samples were collected from Hayatabad Medical Complex from November 2018 to May 2019. This cross-sectional study was conducted at the department of Microbiology, Institute of Pathology and Diagnostic Medicine, Khyber Medical University Peshawar, Pakistan. A total of 369 high vaginal swabs were collected. Candida was isolated by vaginal swabs inoculation on Sabouraud’s dextrose agar (SDA). Colonies on SDA were inoculated on Candida CHROM agar to identify candida species. Wet film microscopy and Gram staining were performed. Biochemical identification was done with 20C AUX. Antifungal susceptibility testing was done by disc diffusion and broth micro-dilution methods to find the resistance pattern of azole drugs. Fluconazole, Clotrimazole, Miconazole, Voriconazole and Itraconazole were the azoles drugs used. Results: Among 43%(n=158) positive candida cases, 44%(n=85) were non pregnant women while 41%(n=73) were pregnant. The Candida species distribution of 158 isolates was as follow; Candida albicans (C. albicans) 46.2%(n=73), Candida krusei (C. krusei) 29.1%(n=46), Candida parapsilosis (C. parapsilosis) 19%(n=30) and Candida glabrata (C. glabrata) 5.7%(n=9). Overall Candida isolates were highly resistant 72%(n=113) to Fluconazole while least resistant 21.5 % (n=34) to Itraconazole. Conclusion: C. albicans is the most prevalent specie involved in Vulvovaginal candidiasis. Candida species were found to be least resistant to Itraconazole followed by Voriconazole, Miconazole, Clotrimazole and Fluconazole. doi: https://doi.org/10.12669/pjms.38.8.5984 How to cite this: Zaman R, Ullah I, Adeeb H, Arif A. Azoles resistance of candida species causing vulvo-vaginitis in reproductive age women at a tertiary care setting. Pak J Med Sci. 2022;38(8):2239-2245. doi: https://doi.org/10.12669/pjms.38.8.5984 This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/3.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.